Metal nonwoven fabric and electrode using same

By using metal fibers with specified voids to make metal nonwoven fabrics, the problems of low liquid permeability and reaction substance arrival efficiency in the prior art are solved, efficient liquid permeability and rapid reaction substance arrival are achieved, and the performance of the electrode is improved.

CN119487250APending Publication Date: 2025-02-18MITSUI MINING & SMELTING CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380051521.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2023-08-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, when metal fibers are used to manufacture electrodes, it is difficult to achieve efficient liquid penetration and effective response substances reach the surface of metal fibers.

Method used

By using metal fibers with specified voids, the liquid is ensured to be efficiently permeated, and by adjusting the average fiber diameter and aspect ratio of the metal fibers, the efficiency of the reaction substance to reach the surface of the metal fibers is improved.

Benefits of technology

It realizes the efficient penetration of liquids in metal non-woven fabrics and the rapid arrival of reaction substances on the metal fiber surface, improving the reactivity and performance of the electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225290980000311
    Figure BDA0005225290980000311
Patent Text Reader

Abstract

Disclosed is a metal nonwoven fabric which contains metal fibers and has liquid permeability. The average fiber diameter of the metal fibers is 20 nm or more and 10 [mu] m or less. The metal nonwoven fabric has a pore distribution peak top diameter of 30 [mu] m or less as measured by mercury intrusion method. The metal nonwoven fabric preferably has a gap distribution peak top diameter of 0.01 [mu] m or more as measured by a mercury intrusion method. The arithmetic mean value of X / Y values, which is the ratio of X to Y in three boundary regions when the length is quartered in the direction of extension of the metal fiber, is preferably 4 or less, where X is the length in the direction of extension of the metal fiber and Y is the length in the direction orthogonal to the direction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a metal nonwoven fabric and an electrode formed using the same. Background Art

[0002] As metal fibers, fine metal fibers with a diameter of about tens of nm to tens of μm are known. Such metal fibers are expected to exhibit physical and chemical properties (such as electrical conductivity, thermal conductivity, luminescence characteristics, catalytic activity, etc.) that are not available in conventional materials due to their fine diameter and high aspect ratio. As prior arts related to the use of metal fibers, for example, the arts described in Patent Document 1 and Non-Patent Document 1 are known.

[0003] Patent Document 1 describes a porous electrode having Cu nanowires produced by reacting and heating a sodium hydroxide aqueous solution, a copper nitrate aqueous solution, an ethylenediamine aqueous solution, and an α-D-glucose aqueous solution. The document describes that the porous electrode has a larger surface area than carbon paper and exhibits a smaller resistivity.

[0004] Non-patent document 1 describes the use of an electrode made of a porous felt using nickel microfibers for alkaline water electrolysis. The document describes that due to the high surface area of ​​the electrode, oxygen bubbles generated by alkaline water electrolysis are easily separated from the electrode, thereby improving the productivity of hydrogen in the electrode.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent document 1: US2019 / 0305322A1

[0008] Non-patent literature

[0009] Non-patent literature 1: F. Yang, et al., Adv. Energy Mater, 2020, 10, 20011174. Summary of the invention

[0010] The technology described in Patent Document 1 and Non-Patent Document 1 utilizes the fine diameter of metal fibers to provide electrodes with a large surface area. When utilizing metal fibers, liquid permeability is sometimes required in order to exert physical and chemical properties, but such an aspect is not mentioned in Patent Document 1 and Non-Patent Document 1. Therefore, the present inventors have conducted in-depth research on the utilization method of metal fibers, and found that if a non-woven fabric is made using metal fibers in a manner having predetermined gaps, liquid efficiently penetrates the non-woven fabric, and the reactant in the liquid immersed in the gap effectively reaches the surface of the metal fiber, thereby making it easy to utilize the desired physical and chemical properties.

[0011] That is, the present invention provides a metal nonwoven fabric, which is a metal nonwoven fabric containing metal fibers and having liquid permeability.

[0012] The metal fibers have an average fiber diameter of 20 nm or more and 10 μm or less.

[0013] The distribution peak top diameter of voids measured by mercury porosimetry is 30 μm or less. DETAILED DESCRIPTION

[0014] The present invention is described below based on its preferred embodiments. The present invention relates to a metal nonwoven fabric. The metal nonwoven fabric of the present invention includes metal fibers made of metal. In the following description, when referred to as "metal fibers", there are cases where it refers to individual fibers or a collection of multiple fibers, depending on the context.

[0015] Metal nonwoven fabric is a sheet-like fiber aggregate with metal fibers as the main body. In this specification, "metal fibers as the main body" refers to the state in which the content of metal fibers in the metal nonwoven fabric is 50% by mass or more. In addition to metal fibers, the metal nonwoven fabric may also contain other constituent materials such as organic fibers, carbon fibers, oxide fibers, etc. In addition, it may also contain materials in shapes other than fibrous shapes. Therefore, the metal nonwoven fabric may also be a sheet-like fiber aggregate containing a variety of constituent materials including metal fibers. However, from the viewpoint of maximizing the advantages of the metal nonwoven fabric, it is preferred that the metal nonwoven fabric is substantially composed only of metal fibers. In this specification, "substantially composed only of metal fibers" means that components other than metal fibers intentionally added to the nonwoven fabric are excluded, and trace components that are inevitably mixed in the manufacturing process of the metal nonwoven fabric are allowed.

[0016] The metal nonwoven fabric may be composed of a single type of metal fibers, or may include a plurality of types of metal fibers including first metal fibers composed of a first metal type and second metal fibers composed of a second metal type.

[0017] The metal nonwoven fabric is in a state where the metal fibers constituting the metal nonwoven fabric are randomly stacked, and the metal fibers are bonded to each other by interweaving and / or welding, etc., thereby maintaining the form of a fabric. In the metal nonwoven fabric, since the metal fibers constituting the metal nonwoven fabric are randomly stacked, a plurality of gaps formed between the fibers by a plurality of fibers are continuous in the thickness direction of the metal nonwoven fabric and in directions other than the thickness direction. Therefore, the metal nonwoven fabric has liquid permeability in the thickness direction and in directions other than the thickness direction.

[0018] The metal nonwoven fabric may be a single-layer structure or a laminated structure formed by laminating multiple layers. In the case where the metal nonwoven fabric is a laminated structure, each layer may be the same or different from each other. The "same" mentioned here means that the metal fibers constituting the metal nonwoven fabric are the same. Such a metal nonwoven fabric can be appropriately manufactured, for example, by the manufacturing method described below.

[0019] The metal nonwoven fabric preferably has liquid permeability as a whole. The liquid permeability of the metal nonwoven fabric is mainly manifested by the fine voids in the nonwoven fabric. The degree of liquid permeability in the metal nonwoven fabric can be appropriately adjusted according to the use of the metal nonwoven fabric. The liquid permeability in the metal nonwoven fabric can be improved, for example, by adjusting the average fiber diameter of the metal fibers in the metal nonwoven fabric and the size of the voids in the metal nonwoven fabric, as described later.

[0020] Liquid permeability is generated by capillary phenomena, and in theory, it is determined by the physical state and chemical state of the surface of the raw material constituting the metal nonwoven fabric, and the relationship between the surface tension of the metal nonwoven fabric and the surface tension of the liquid determined thereby, in addition to the diameter of the pores. Here, in the present invention, liquid permeability is defined as a characteristic value that can be measured by the following method.

[0021] First, cut a sample of 25mm in length and 5mm in width from the dry metal nonwoven fabric. Next, measure the thickness and mass of the sample. Hang the sample from above a glass container (circular with a bottom diameter of 15mm) filled with water, and put it in such a way that the front 5mm of the sample is immersed in the water in the container. As a result, the water penetrates into the sample and is sucked up. After 15 minutes, take out the sample from the container and measure the mass of the water remaining in the glass container. The volume of the sample is calculated based on the dimensions of the outer contour of the sample before water absorption, and the average amount of water absorbed per unit volume is calculated, and this value is 0.4mL / cm 3 The above samples are judged as "liquid-permeable" in this specification. The specific method of measuring the volume will be described later.

[0022] As long as the metal nonwoven fabric has liquid permeability as a whole, for example, it can be set as a three-layer metal nonwoven fabric in which one or more layers of mesh or perforated foil (hereinafter also referred to as "mesh, etc.") are arranged between two layers of metal nonwoven fabric. Alternatively, it can be set as a three-layer or more metal nonwoven fabric in which a layer of metal nonwoven fabric is arranged between two layers of mesh, etc. In this way, the strength of the metal nonwoven fabric can be improved. The average pore size (JIS Z8801) of the mesh or the average opening diameter of the perforated foil is preferably less than 1000 μm, and can also be less than 900 μm. The mesh, etc. can be made of metal or non-metal. In the case where the mesh, etc. is made of metal, the type of metal constituting the mesh, etc. and the type of metal constituting the metal nonwoven fabric can be the same or different.

[0023] From the viewpoint of improving the liquid permeability in the metal nonwoven fabric and allowing the reactant in the permeated liquid to reach the metal fibers constituting the metal nonwoven fabric in a short time, the average fiber diameter of the metal fibers is preferably from 20 nm to 10 μm, more preferably from 20 nm to 6 μm, further preferably from 20 nm to 5 μm, further preferably from 30 nm to 3 μm, further preferably from 90 nm to 3 μm, and particularly preferably from 120 nm to 2.5 μm.

[0024] From the viewpoint of improving the liquid permeability in the metal nonwoven fabric and maintaining the mechanical strength and facilitating the manufacture of the metal nonwoven fabric, the average length of the metal fibers is preferably 0.5 μm to 5000 μm, more preferably 0.5 μm to 2000 μm, further preferably 1 μm to 500 μm, further preferably 3 μm to 200 μm, further preferably 3 μm to 150 μm, and particularly preferably 3 μm to 90 μm.

[0025] The average fiber diameter and average length of the metal fibers in the metal nonwoven fabric may be the same or different on one side and the other side of the metal nonwoven fabric. Alternatively, when the metal nonwoven fabric is observed along the thickness direction, the average fiber diameter and average length of the metal fibers may be changed in a stepwise manner, continuously, or in combination thereof. Such a metal nonwoven fabric is formed, for example, by using a plurality of metal fibers.

[0026] As described above, the metal fibers in the metal nonwoven fabric are preferably very thin and long. By making the metal fibers have such an average fiber diameter and average length, the liquid permeability in the metal nonwoven fabric can be improved, and the reactant in the permeated liquid can reach the surface of the metal fibers constituting the metal nonwoven fabric in a short time. In addition, it is easy to control these characteristic values ​​of the metal fibers, and in addition, it is easy to improve its operability.

[0027] From the viewpoint of improving the liquid permeability in the metal nonwoven fabric and allowing the reactant in the permeated liquid to reach the metal fibers constituting the metal nonwoven fabric in a short time, the aspect ratio of the metal fiber (length of the metal fiber [m] / fiber diameter of the metal fiber [m]) is preferably 5 to 5000, more preferably 13 to 3000, further preferably 20 to 3000, further preferably 20 to 1500, further preferably 20 to 800.

[0028] The average fiber diameter of the metal fibers in the metal nonwoven fabric can be measured by the following method. In detail, the metal nonwoven fabric is first observed using a scanning electron microscope (hereinafter also referred to as "SEM"). The metal nonwoven fabric is observed at a magnification that allows easy observation of the fiber diameter of the metal fibers constituting the metal nonwoven fabric, specifically at any magnification between 1000 times and 10000 times. From the SEM image of the obtained metal nonwoven fabric, 10 arbitrary metal fibers other than the metal fibers that are entangled with other metal fibers and cannot be measured individually are taken out, and the fiber diameter of each metal fiber is calculated. The arithmetic average is performed to obtain the average fiber diameter of the metal fibers.

[0029] The average length of the metal fibers in the metal nonwoven fabric can be measured by the following method. In detail, the metal nonwoven fabric is first observed using an SEM. The metal nonwoven fabric is observed at a magnification that allows easy observation of the length of the metal fibers constituting the metal nonwoven fabric, specifically at any magnification between 200 and 2000 times. From the SEM image of the obtained metal nonwoven fabric, 20 arbitrary metal fibers other than metal fibers that are entangled with other metal fibers and cannot be measured individually are taken out. When the metal fibers are exposed from one screen of the SEM image, a plurality of continuous SEM images are panoramically connected to thereby calculate the length of each metal fiber. The arithmetic average is performed to obtain the average length of the metal fibers.

[0030] The metal fibers in the metal nonwoven fabric may have a substantially uniform average fiber diameter over the entire length, or may have a bead-like shape in which the average fiber diameter is different. The metal fibers preferably have at least one end that is tapered. "Tapered shape" refers to a shape in which the thickness gradually decreases toward the front end when observing the end region of the metal fiber. By making at least one end of the metal fiber tapered, the area in which the metal fibers are in contact with each other is expanded, which is advantageous from the perspective of the performance of electrical conductivity and thermal conductivity and the maintenance of mechanical strength. Furthermore, according to the metal fibers having at least one end that is tapered, the convexity and concavity of the contact surface are reduced compared to the metal fibers having the same average fiber diameter, so that the deviation in the size of the voids in the metal nonwoven fabric can be suppressed.

[0031] From the viewpoint of making this advantage more significant, the angle of the tapered tip is preferably 90 degrees or less, more preferably 80 degrees or less, further preferably 70 degrees or less, and may be 60 degrees or less, 50 degrees or less, or 45 degrees or less.

[0032] The angle of the front end of the tapered shape is measured according to the following steps. First, as described above, the fiber diameter of the metal fiber is measured based on SEM at any magnification between 1000 times and 10000 times. Next, a circular arc with a diameter of the same length as the fiber diameter of the metal fiber is drawn with the front end of the end of the metal fiber as the center, and two intersections of the circular arc and the metal fiber are obtained. The angle between the two intersections and the front end of the end of the metal fiber connected by a straight line is measured as the angle of the front end. It should be noted that when the cross-section of the end of the metal fiber is linear or approximately linear, its center is taken as the front end of the end. In addition, when the cross-section of the end of the metal fiber is linear or approximately linear, when the length of its cross-section exceeds half of the fiber diameter of the metal fiber, the metal fiber is not taken as the object of measurement. The measurement is performed on more than 10 metal fibers, and the arithmetic mean is taken as the angle of the front end of the tapered shape.

[0033] The shape of the metal fiber in the metal nonwoven fabric is typically a fiber extending in one direction, but the metal fiber may or may not have a main chain portion extending in one direction and a branch structure branching from the middle of the main chain portion. From the viewpoint of improving liquid permeability by controlling the size of the voids in the metal nonwoven fabric, the metal fiber is preferably a non-branch structure having only a main chain portion. On the other hand, from the viewpoint of making the metal nonwoven fabric present a bulky structure and further improving the contact area with the liquid, the metal fiber preferably has one or more branch portions. In addition, the metal nonwoven fabric can be formed using only metal fibers having a non-branch structure having only a main chain portion, or can be formed using only metal fibers having one or more branch portions, or can be formed by a combination of them.

[0034] The type of metal constituting the metal fiber in the metal nonwoven fabric is not particularly limited, and various metals can be used. If the balance between high electrode conductivity and ease of industrial utilization is considered, copper, silver, gold, nickel, lead, palladium, platinum, cobalt, tin, iron, zinc or bismuth or alloys containing these metals can be listed. The metal constituting the metal fiber is particularly preferably copper, nickel, tin or zinc or alloys containing these metals. Alternatively, fibers can also be formed in a state where crystals of these various metals and crystals of alloys are mixed. Among them, fibers with copper or copper alloy as the base material are particularly preferred. It should be noted that "using copper or copper alloy as the base material" means that the proportion of copper in the metal fiber is more than 60% by mass. It should be noted that, as a state where crystals of various metals and crystals of alloys are mixed, a state where crystals of different types of metals such as Cu crystal-Ni crystal-Cu crystal-Ni crystal are connected can be listed.

[0035] The surface of the metal fiber in the metal nonwoven fabric may be covered with a substance other than metal. The "covering" mentioned here includes the case where the metal constituting the metal fiber is chemically bonded to the substance other than metal and the case where the metal constituting the metal fiber is physically adsorbed to the substance other than metal. The metal fiber may be in any one of the covering states, or may be in two covering states.

[0036] As materials other than metal covering the metal fibers in the metal nonwoven fabric, for example, oxides, sulfides, organic matter, carbon materials, semiconductor materials, ferroelectric materials, magnetic materials, MOF (metal organic structure), PCP (porous coordination polymer), etc. Among them, when using the metal nonwoven fabric as an electrode catalyst, it is preferred to cover the metal fibers with oxides, organic matter, carbon materials, and semiconductor materials.

[0037] There is no particular limitation on the method of coating metal fibers with other substances. Examples include, for example, a method of electrolytically plating metal fibers in an electrolytic bath containing a substance for coating after the metal fibers are precipitated by the method described below; a cationic electrodeposition coating method; an anionic electrodeposition coating method; a surface oxidation treatment method (forming a film by reacting with a chemical substance in a liquid by electro-oxidizing or chemically oxidizing the surface); a displacement plating method; a chemical plating method; a method of coating a metal fiber with a catalyst for these plating methods and then coating the target substance; a liquid phase precipitation method; an electrophoresis method; a method utilizing a surface potential difference; a sol-gel method; a gel-sol method; a polyol method; a spray method; a cold spray method; a spray drying method; a dip coating method; a vapor deposition method; a sputtering method; a CVD method; a thermal decomposition method; a plasma film forming method; an immersion method; an atomic layer deposition method (ALD method); a coating method; an ink method; a fine particle coating method or a coating method utilizing a dry method.

[0038] The metal fiber in the metal nonwoven fabric may be composed of a core portion composed of metal and a shell portion, wherein the core portion is composed of metal and the shell portion is arranged on the surface of the core portion and is composed of a metal other than the metal. In other words, the metal fiber in the metal nonwoven fabric may be composed of different types of metals stacked together.

[0039] The core part constitutes the main part of the metal fiber. The shell part may be arranged on the entire surface of the core part, or the shell part may exist in a manner of covering a part of the surface of the core part.

[0040] In addition, the boundary between the core portion and the shell portion may be clear, or a portion of the boundary may be unclear within a range in which the core portion and the shell portion can be distinguished.

[0041] Examples of the metal constituting the core include copper, silver, gold, nickel, lead, palladium, platinum, cobalt, tin, iron, zinc, bismuth, or alloys containing these metals. Examples of the metal constituting the shell include copper, silver, nickel, tin, zinc, lead, iron, cobalt, platinum, gold, palladium, etc., as long as the metal is different from the metal constituting the core.

[0042] The method for producing the metal fiber composed of the core and the shell is not particularly limited. Examples thereof include a method in which, for example, the metal fiber is deposited by the method described below and then electrolytically plated in an electrolytic bath containing a substance for covering; a displacement plating method; a chemical plating method; a method in which a catalyst for these platings is attached to the metal fiber and then the target substance is plated; an electrophoresis method; a method utilizing a surface potential difference; a polyol method; a spray method; a cold spray method; a spray drying method; a sputtering method; a CVD method; a thermal decomposition method; a plasma film forming method; an atomic layer deposition method (ALD method); an ink method; a fine particle coating method or a coating using a dry method.

[0043] The metal fiber in the metal nonwoven fabric is preferably a polycrystalline structure in which a plurality of crystals are connected along the extension direction of the metal fiber (hereinafter also referred to as the "length direction"). According to such metal fibers, due to their characteristic crystal structure, the temperature at which the metal fibers are fused to each other decreases, and the metal fibers can be fused at a lower temperature. As a result, the metal nonwoven fabric can be formed under stable conditions at a lower temperature. In addition, the metal fiber is more likely to take a curved shape than a straight shape, so the mechanical strength of the metal nonwoven fabric can be improved. In addition, the crystal surface that is easily oxidized on the side of the metal fiber will not be exposed preferentially, and the oxidation of the side of the metal fiber is suppressed. Furthermore, as described above, since the end of the metal fiber can be set to a tapered shape, the area in which the metal fibers are in contact with each other is expanded, and it is easy to show electrical conductivity and thermal conductivity.

[0044] It should be noted that, when the metal fiber has a bent portion, the “extending direction” of the metal fiber refers to the tangential direction thereof.

[0045] The crystal structure of the metal fiber is described in detail. For the crystal of the metal constituting the metal fiber, when the length along the length direction of the metal fiber is set to X and the length along the direction orthogonal to the length direction (hereinafter also referred to as the "width direction") is set to Y, the ratio of X to Y, that is, the value of X / Y is preferably 4 or less.

[0046] The crystals of the metal constituting the metal fiber in this way preferably have no large difference in the length in the length direction and the length in the width direction, and are in a shape having a roughly isotropic shape. The average fiber diameter of the metal fiber is as described above, which is more than 20nm and less than 10μm, so it can be understood that the crystals of the metal constituting the metal fiber are usually fine. Since the crystals of the metal constituting the metal fiber in the metal non-woven fabric have such a structure, as described above, the temperature at which the metal fibers are fused to each other decreases, and the metal fibers can be fused at a lower temperature, and as a result, the metal non-woven fabric can be formed under a more stable condition at a lower temperature. In addition, the metal fiber is more likely to take a curved shape than a straight shape, so the mechanical strength of the metal non-woven fabric can be improved. In addition, the crystal face that is easily oxidized on the side of the metal fiber will not be preferentially exposed, and the oxidation of the side of the metal fiber is suppressed. Furthermore, since the end of the metal fiber can be set to a tapered shape, the area in contact with each other by the metal fibers is expanded, and it is easy to show electrical conductivity and thermal conductivity.

[0047] From the viewpoint of making this advantage more remarkable, the value of X / Y is more preferably 3 or less, and further preferably 2.5 or less.

[0048] The above-mentioned X / Y value is calculated by the following method. First, for one metal fiber constituting the metal nonwoven fabric, the length is divided into four equal parts along the length direction, and the crystals located in the three boundary areas at this time are measured respectively. Similarly, the measurement is repeated for two or more metal fibers. Regarding the calculation of the value, the average value of one metal fiber is calculated based on the X / Y value of each part in the metal fiber (X / Y is not calculated by the average value of X and the average value of Y, but the X / Y value of each part is averaged), and then, the arithmetic mean value is calculated from the X / Y of each of the read multiple metal fibers. The first decimal place of the arithmetic mean is rounded off. It should be noted that it is recorded as "the boundary area when the length is divided into four equal parts along the length direction", but when the measurement at the boundary area cannot be performed due to measurement reasons, the part close to the boundary area (for example, the part within 10% of the length of the metal fiber on the left and right of the boundary area) is measured.

[0049] The "crystal" mentioned in this specification refers to a grain, and its size can be measured by the electron backscatter diffraction (hereinafter also referred to as "EBSD") method. It should be noted that the grain is a concept different from the crystallite size obtained by the XRD pattern. In the case where the crystal mentioned in this specification is a twin, each crystal constituting the twin is defined as a different crystal. In addition, even if it is impossible to confirm whether the crystal is a twin, even if a part of the line representing the grain boundary is seen in EBSD, it is defined as a different crystal, and the value of X / Y is obtained for each crystal.

[0050] When the value of X / Y is 4 or less, the values ​​of X and Y are not limited. From the viewpoint of being able to lower the fusion temperature of the metal fiber, the value of X itself is preferably 10 μm or less, more preferably 5 nm or more and 2 μm or less, and even more preferably 10 nm or more and 500 nm or less. From the same viewpoint, the value of Y itself is preferably 3 μm or less, more preferably 5 nm or more and 1 μm or less, and even more preferably 10 nm or more and 400 nm or less.

[0051] On the other hand, when the value of X / Y exceeds 4, the metal fiber is characterized only by the above-mentioned value of Y. That is, the value of Y is preferably 10 nm or less.

[0052] Y being less than 10 nm means a thin state with a width of only about 100 or less atoms when expressed in terms of the number of metal atoms. This is the same as the design concept of setting the value of X / Y to less than 4, and has the same meaning as fine crystals. Therefore, according to such metal fibers, the temperature of the metal fiber fusion can be reduced in the metal nonwoven fabric of the present invention. It should be noted that as long as Y is less than 10 nm, the value of X / Y is not limited.

[0053] The above-mentioned Y value is calculated by the following method. First, for one metal fiber, the length is divided into four equal parts along the length direction, and the value of Y of each crystal located in the three boundary areas at this time is measured. Similarly, the measurement is repeated for two or more metal fibers, and the value obtained by arithmetic averaging these values ​​is obtained. The first decimal place of the arithmetic mean is rounded off. It should be noted that it is recorded as "the boundary area when the length is divided into four equal parts along the length direction", but when the measurement at the boundary area cannot be performed due to measurement reasons, the part close to the boundary area (for example, the part within 10% of the length of the metal fiber on the left and right of the boundary area) is measured.

[0054] The metal fibers in the metal nonwoven fabric are also characterized by the crystal orientation of the metal from which they are composed.

[0055] Specifically, when focusing on the crystals existing in the three boundary regions when the length of the metal fiber is divided into four equal parts along the extending direction, the existence ratio of the crystal grains forming the

[110] orientation evaluated by electron diffraction or EBSD using a transmission electron microscope (hereinafter also referred to as "TEM") within the range of ±30° in the extending direction of the metal fiber is preferably 50% or less, more preferably 45% or less, and further preferably 40% or less. Satisfying such a relationship means that the

[110] orientation of the crystal is not preferentially oriented in the length direction of the metal fiber.

[0056] The existence ratio of grains forming a

[110] orientation is calculated as follows: two or more metal fibers are randomly extracted from the metal nonwoven fabric, and a boundary line is drawn along the length direction of each metal fiber to divide the length into four equal parts, and the three boundary areas of the boundary are measured and calculated.

[0057] When evaluating by electron diffraction using TEM, the percentage of grains forming a

[110] orientation is measured at a total of more than 6 locations (for example, 6 locations when 2 metal fibers are extracted, and 15 locations when 5 metal fibers are extracted) at the midpoint of the boundary line in each boundary region.

[0058] When evaluating by EBSD, measurement is performed at three points that divide the boundary line into four equal parts in each boundary region, totaling 18 or more points (for example, 18 points when two metal fibers are extracted, and 45 points when five metal fibers are extracted).

[0059] The first decimal place of percentage is rounded off.

[0060] When observing the

[110] oriented grains using TEM, electrons are passed through the metal fiber for observation. However, if the fiber diameter of the metal fiber is greater than 200 nm, the electrons cannot pass through the metal fiber, and the target electron diffraction pattern cannot be obtained. Therefore, when the fiber diameter of the metal fiber is greater than 200 nm, EBSD is used to evaluate the existence ratio of the

[110] oriented grains. It should be noted that it is recorded as "the boundary area when the length is divided into four equal parts along the extension direction", but when the measurement at the boundary area cannot be performed due to measurement reasons, the part close to the boundary area (for example, the part within 10% of the length of the metal fiber on the left and right of the boundary area) is measured.

[0061] Generally, the side surfaces of metal fibers that are preferentially oriented in the

[110] orientation in the longitudinal direction are easily oxidized, which is one reason why the resistance of the metal fibers in the width direction increases. In contrast, metal fibers that are not grown in the

[110] orientation in the longitudinal direction are difficult to oxidize.

[0062] Similarly, from the viewpoint that the metal fiber constituting the metal nonwoven fabric is not easily corroded, the length of the metal fiber is divided into four equal parts along its extension direction, and for the crystals existing in the three boundary regions at this time, the existence ratio of the grains forming the

[111] orientation within the range of ±30° in the extension direction of the metal fiber evaluated by electron diffraction of TEM or EBSD is preferably 50% or more, more preferably 52% or more, and further preferably 60% or more. On the other hand, as an upper limit of the existence ratio, about 80% is realistic.

[0063] The existence ratio of grains forming a

[111] orientation is calculated as follows: two or more metal fibers are randomly extracted from the metal nonwoven fabric, and a boundary line is drawn along the length direction of each metal fiber to divide the length into four equal parts, and three boundary areas of the boundary are measured to calculate.

[0064] When evaluating by electron diffraction using TEM, the percentage of grains forming a

[111] orientation is measured at a total of more than 6 locations (for example, 6 locations when 2 metal fibers are extracted, and 15 locations when 5 metal fibers are extracted) at the midpoint of the boundary line in each boundary region.

[0065] When evaluating by EBSD, measurement is performed at three points that divide the boundary line into four equal parts in each boundary region, totaling 18 or more points (for example, 18 points when two metal fibers are extracted, and 45 points when five metal fibers are extracted).

[0066] The first decimal place of percentage is rounded off.

[0067] Such a relationship means that the

[111] orientation is preferentially oriented in the length direction of the metal fiber. The

[111] orientation of the crystal is preferentially oriented in the length direction, which means that the (100) plane that is easily corroded is not exposed on the side surface in crystallography, so it is preferred. It should be noted that it is recorded as "the boundary area when the length is divided into four equal parts along the extension direction", but when the measurement at the boundary area cannot be performed due to measurement reasons, the part close to the boundary area (for example, the part within 10% of the length of the metal fiber on the left and right of the boundary area) is measured.

[0068] When the length of the metal fiber is divided into four equal parts along its extension direction, for the crystals existing in the three boundary areas at this time, the existence ratio of grains forming

[100] orientation,

[110] orientation and

[111] orientation within the range of ±30° in the extension direction of the metal fiber evaluated by electron diffraction of TEM or EBSD is preferably less than 50%, and more preferably less than 40%.

[0069] The existence ratio of grains forming

[110] ,

[111] , and

[100] orientations is calculated as follows: two or more metal fibers are randomly extracted from the metal nonwoven fabric, and boundary lines are drawn along the length direction of the metal fibers to divide the length into four equal parts, and the three boundary areas of the boundary are measured and calculated.

[0070] When evaluating by electron diffraction using TEM, the percentage of grains forming

[110] ,

[111] , and

[100] orientations is measured at a total of more than 6 locations (for example, 6 locations when 2 metal fibers are extracted, and 15 locations when 5 metal fibers are extracted) at the midpoint of the boundary line in each boundary region.

[0071] When evaluating by EBSD, measurement is performed at three points that divide the boundary line into four equal parts in each boundary region, totaling 18 or more points (for example, 18 points when two metal fibers are extracted, and 45 points when five metal fibers are extracted).

[0072] The first decimal place of the percentage is rounded off. It should be noted that, although it is described as "the boundary region when the length is divided into four equal parts along the extending direction", if the measurement at the boundary region cannot be performed due to measurement reasons, the portion close to the boundary region (for example, the portion within 10% of the length of the metal fiber on the left and right of the boundary region) is measured.

[0073] The metal fibers contained in the metal non-woven fabric are in such a relationship, which means that the crystals of the metal constituting the metal fibers are randomly oriented. The random orientation direction of the crystals of the metal constituting the metal fibers means that the crystals of the metal constituting the metal fibers are polycrystalline, which means that the crystals are small. Since the crystals are small, the temperature at which the metal fibers are fused to each other decreases, and the metal fibers can be fused at a lower temperature. As a result, the metal non-woven fabric can be formed under stable conditions at a lower temperature. Furthermore, "the orientation direction of the crystals is random" means that the side surface of the metal fiber, the (100) surface, is not preferentially exposed, which means that the oxidation of the side surface of the metal fiber is not promoted.

[0074] In the metal nonwoven fabric, the number of metal fibers having a curved portion with a radius of curvature of 5 times or less than the length of the metal fiber preferably accounts for more than 20% of the total number of metal fibers in the metal nonwoven fabric. In this way, the metal fibers constituting the metal nonwoven fabric originally have curved portions, which can improve the resistance of the metal nonwoven fabric when the metal nonwoven fabric is compressed, stretched, or subjected to bending stress, and is therefore preferred. Furthermore, in the metal nonwoven fabric, there is also the advantage that it is easy to achieve contact across a plurality of the metal fibers in the lateral (width) direction of the metal fibers, and as a result, it is easy to exhibit electrical conductivity and thermal conductivity.

[0075] The radius of curvature is calculated as follows. First, the metal nonwoven fabric is observed by SEM. The two ends of the metal fiber in the SEM image are connected with a straight line, and its length (chord length) is measured. Then, an auxiliary line orthogonal to the straight line is drawn from the midpoint of the straight line toward the metal fiber side, and the distance (sagittal) between the midpoint and the position intersecting the metal fiber is measured. The radius of curvature is calculated according to the following calculation formula.

[0076] r=(C×C) / (8×h)+h / 2

[0077] (In the formula, r is the radius of curvature, C is the chord length, and h is the sagittal height.)

[0078] The above-mentioned radius of curvature is preferably not less than 0.5 μm and not more than 1000 μm.

[0079] It should be noted that, when the metal fiber in the metal nonwoven fabric is bent, the metal fiber is approximately in a shape having a bent portion, and the radius of curvature is calculated according to the above calculation formula. In addition, when the two ends of the metal fiber are connected by a straight line, when the straight line crosses the metal fiber, the radius of curvature is measured as a different metal fiber with the cross-section portion as the boundary.

[0080] The metal nonwoven fabric may contain particles having shapes other than metal fibers. However, since the metal nonwoven fabric is produced based on the idea of ​​randomly stacking the fibers to control the gaps in the metal nonwoven fabric, it is preferred that particles having shapes other than fibers not be present in the metal nonwoven fabric as much as possible from the viewpoint of improving the liquid permeability in the metal nonwoven fabric even when deformed such as bending and stretching.

[0081] When the ratio of particles having shapes other than fibers in the metal nonwoven fabric is defined as the "irregular shape ratio", the irregular shape ratio is preferably 50% or less, more preferably 40% or less, and further preferably 30% or less. If the metal nonwoven fabric is manufactured by the manufacturing method described below, the irregular shape ratio of the metal nonwoven fabric can be easily made 50% or less.

[0082] The irregular shape ratio is obtained by observing the sample to be measured by SEM in a field of view where the fiber diameter and length of the metal fiber are 5 to 30 times the average fiber diameter and average length of the metal fiber, and calculating the percentage of [area of ​​irregular shape material / area of ​​metal nonwoven fabric] to obtain the irregular shape ratio. "Irregular shape" refers to a shape other than the fiber.

[0083] From the viewpoint of improving the liquid permeability in the metal nonwoven fabric and allowing the reactant in the permeated liquid to reach the surface of the metal fiber constituting the metal nonwoven fabric in a short time, in the metal nonwoven fabric, the distribution peak top diameter of the voids measured by the mercury intrusion method is preferably 30 μm or less, more preferably 0.01 μm or more and 30 μm or less, further preferably 0.02 μm or more and 25 μm or less, further preferably 0.05 μm or more and 20 μm or less, and further preferably 0.1 μm or more and 20 μm or less.

[0084] In addition, when two or more peaks are observed in the void distribution measured by mercury intrusion porosimetry, it is preferred that the distribution peak top diameter of the highest peak satisfies the above range because the above advantages become more significant.

[0085] When the voids in the metal nonwoven fabric, i.e., the voids between the metal fibers in the metal nonwoven fabric, are less than 30 μm, the distribution peak top diameter of the voids is obtained by mercury intrusion porosimetry. It should be noted that when the voids exceed 30 μm, the size of the voids is obtained by the average value of the equivalent sphere diameters of the pores obtained by dividing the voids through image analysis measured by X-ray CT.

[0086] The mercury intrusion method was measured using Autopore IV 9510 manufactured by Micromeritics Instrument Corporation. During the measurement, the mercury intrusion force was about 0.5 to 60,000 psi (about 3 kPa to 400 MPa), the measurement mode was a pressure increase (intrusion) process, the mercury contact angle was 141.3°, and the mercury surface tension was 484 dyn / cm.

[0087] In the X-ray CT measurement, the X-ray CT measurement was performed using SKYSCAN AN2214 manufactured by Bruker, and the average value of the equivalent spherical diameters of the pores obtained by dividing the voids was determined using the image analysis software Avizo 3D manufactured by Thermo Fisher Scientific.

[0088] The porosity in the metal nonwoven fabric can be calculated as the volume of the space existing therein relative to the volume based on the dimensions of the outer contour of the metal nonwoven fabric.

[0089] Specifically, first, the volume V1 of the metal nonwoven fabric is calculated from the lengths of the metal nonwoven fabric in the longitudinal and transverse directions and the thickness of the metal nonwoven fabric measured by the method described later. Next, the mass of the metal nonwoven fabric is measured, and the volume V2 of the metal nonwoven fabric is calculated from the specific gravity of the metal constituting the metal nonwoven fabric. The value V3 obtained by subtracting the volume V2 calculated from the mass of the metal nonwoven fabric from the volume V1 of the metal nonwoven fabric is taken as the volume of the space. The percentage of the volume V3 of the space existing in the metal nonwoven fabric relative to the volume V1 of the metal nonwoven fabric is calculated and taken as the porosity.

[0090] From the viewpoint of increasing the amount of liquid that permeates the metal nonwoven fabric, the porosity is preferably 50% or more, more preferably 60% or more, further preferably 70% or more, and further preferably 80% or more. In addition, from the viewpoint of maintaining the strength of the metal nonwoven fabric, the porosity is preferably 99% or less.

[0091] The distribution peak diameter of the voids in the above-mentioned metal nonwoven fabric measured by mercury intrusion, the equivalent spherical diameter (average) of the pores obtained by dividing the voids by X-ray CT method, and the porosity are achieved, for example, by adjusting the average fiber diameter and average length of the metal fiber. In addition, it can also be achieved by intentionally mixing a plurality of metal fibers having different average fiber diameters and average lengths. In addition or in lieu thereof, it can also be achieved by appropriately adjusting the conditions in the manufacturing method of the metal nonwoven fabric described later.

[0092] The metal nonwoven fabric with such a structure has appropriate gaps in the metal nonwoven fabric, so the liquid permeability, especially the permeability of aqueous liquid in the metal nonwoven fabric can be improved by the capillary phenomenon caused by the size of the gap, etc. In other words, the amount of liquid absorbed by the unit volume of the outer contour of the metal nonwoven fabric in a dry state can be increased within a certain period of time. Thus, for example, when a solution containing a reactant contacts the metal nonwoven fabric, the solution immediately penetrates into the gap in the metal nonwoven fabric, so the reactant easily reaches the surface of the metal fiber forming the gap or its extremely vicinity. In addition, since the gap in the metal nonwoven fabric relative to the diffusion speed of the reactant in the solution is sufficiently narrow, the reactant can reach the surface of the metal fiber constituting the metal nonwoven fabric in a short time.

[0093] On the other hand, when the metal nonwoven fabric having a gap wider than the appropriate gap contacts with the solution containing the reactant, the capillary phenomenon will not fully occur compared with the metal nonwoven fabric of the present invention, so the solution will not fully penetrate into the metal nonwoven fabric. That is, the liquid permeability to the liquid cannot be improved. In addition, due to the wide gap in the metal nonwoven fabric relative to the diffusion speed of the reactant in the solution, it is difficult for the reactant to reach the surface of the metal fiber constituting the metal nonwoven fabric in a short time.

[0094] Therefore, according to the metal nonwoven fabric of the present invention, when the metal nonwoven fabric is brought into contact with a solution, the reaction of the reactant contained in the solution is easy to occur efficiently, and the desired physical and chemical properties are easy to be exerted. It should be noted that in this specification, "aqueous liquid" refers to a liquid (solution, dispersion, emulsion, etc.) containing 5% by mass or more of water.

[0095] It should be noted that the advantages of the metal nonwoven fabric of the present invention are not only exhibited for water-based liquids, but also for organic solvent-based liquids, regardless of the type of solvent. This is because the surface of the metal fiber constituting the metal nonwoven fabric is treated with a substance having an affinity for the solvent in contact with the metal nonwoven fabric, thereby being able to exhibit liquid permeability to various solvents.

[0096] From the viewpoint of improving the liquid permeability in the metal nonwoven fabric, the viewpoint of improving the reactivity with the liquid when the metal nonwoven fabric is used for example as an electrode, and the viewpoint of satisfying the practicality as an electrode, in the metal nonwoven fabric, the average thickness is preferably 3 μm or more, more preferably 50 μm or more, and further preferably 90 μm or more. By making the average thickness of the metal nonwoven fabric more than 3 μm, it is possible to maintain a self-supporting state as a metal nonwoven fabric. In addition, the upper limit of the average thickness of the metal nonwoven fabric depends on the purpose, so it cannot be generalized, and can be less than 50 mm, or less than 30 mm, or less than 10 mm, or less than 5 mm, or less than 2 mm.

[0097] The average thickness of the metal nonwoven fabric can be measured by the following method.

[0098] First, cut the metal non-woven fabric into a length of 2cm × width of 2cm to make a cut piece of the metal non-woven fabric. However, in the case where the cut piece to be measured cannot be made into a cut piece of this size, make a cut piece as large as possible. Next, place the cut piece on a flat plate, and place a flat plate weighing 1g with a size larger than the size of the cut piece on it. In this state, use a vernier caliper to measure the distance from the lower surface of the flat plate under the cut piece to the upper surface of the flat plate on the cut piece. Subtract the thickness of the two pre-measured flat plates from the measured value obtained, and use it as the thickness of the metal non-woven fabric. Measure the thickness of the cut pieces collected from any three or more places of the metal non-woven fabric, and take their arithmetic mean as the average thickness.

[0099] When the thickness of the metal nonwoven fabric exceeded 10 μm, it was measured using a vernier caliper as described above. When it was 10 μm or less, the average thickness was measured using a cross-sectional SEM image.

[0100] From the viewpoint that the liquid is allowed to penetrate into the metal nonwoven fabric and the reactant in the liquid reaches the surface of the metal fibers constituting the metal nonwoven fabric in a short time without excessive or insufficient reaction on the surface of the metal fibers, the specific surface area of ​​the metal nonwoven fabric is preferably 0.02 m 2 / g or more and 22m 2 / g or less, more preferably 0.1m 2 / g or more and 10m 2 / g or less, more preferably 0.2m 2 / g or more and 3m 2 / g or less, and more preferably 0.25m 2 / g or more and 2m 2 / g or less.

[0101] The specific surface area of ​​the metal nonwoven fabric can be measured by the following method.

[0102] About the specific surface area of ​​0.1m 2 / g or more of metal nonwoven fabric, for example, the specific surface area is measured by krypton gas adsorption-BET multipoint method using a specific surface area / pore size distribution measuring device BELSORP-max manufactured by BEL Japan Inc. 2 / g of metal nonwoven fabric, for example, is measured by X-ray CT using a nanofocus X-ray CT scanner SKYSCANAN2214 manufactured by Bruker, and the specific surface area is calculated by quantifying the structural features of the three-dimensional object to be measured, such as the area and volume of the object, using the image analysis software Avizo 3D manufactured by Thermo Fisher Scientific based on the obtained three-dimensional information.

[0103] The specific surface area of ​​the metal nonwoven fabric can be adjusted by, for example, forming the metal nonwoven fabric using materials having metal fibers with different average fiber diameters, or by laminating a plurality of types of metal nonwoven fabrics.

[0104] From the viewpoint that the liquid is allowed to penetrate into the metal nonwoven fabric and the reactant in the liquid reaches the surface of the metal fiber in a short time without excessive or insufficient reaction on the surface of the metal fiber, the apparent density of the metal nonwoven fabric is preferably 0.01 g / cm 3 Above and 2.0g / cm 3 Below, more preferably 0.05g / cm 3 Above and 1.7g / cm 3 Below, more preferably 0.1 g / cm 3 Above and 1.4g / cm 3 the following.

[0105] The apparent density is determined by calculating the volume V1 of the metal nonwoven fabric and the mass of the metal nonwoven fabric by the above-mentioned method, and dividing the mass by the volume V1.

[0106] The apparent density of the metal nonwoven fabric can be adjusted by, for example, increasing the average fiber diameter of the metal fibers, increasing the average thickness of the metal fibers, or laminating a plurality of types of metal nonwoven fabrics.

[0107] Next, the preferred method for manufacturing the metal nonwoven fabric of the present invention is described. In the manufacture of the metal fibers that mainly constitute the metal nonwoven fabric, it is preferred to use an electrolytic method. By selecting appropriate additives and performing an electrolytic method under appropriate electrolytic conditions, metal fibers with a low degree of aggregation can be easily obtained. If such metal fibers are piled up and sintered, the metal fibers are easily sintered at a low temperature. As a result, a metal nonwoven fabric can be easily formed. In addition, according to the electrolytic method, it has the advantage of being easy to control the metal fibers into a desired shape. Furthermore, the electrolyte can be reused repeatedly, and less liquid is required when manufacturing the metal nonwoven fabric, so the amount of waste liquid to be treated can be reduced at the same time.

[0108] When the metal fiber is produced by electrolysis, the following process can be illustrated, for example: the anode and cathode are immersed in a sulfuric acid electrolyte containing a metal element source, and a direct current is passed therethrough to perform electrolytic reduction, so that the metal fiber is precipitated on the surface of the cathode. A preferred current density is 50 A / m 2 Above and 600A / m 2 Next, when manufacturing a metal nonwoven fabric, the following steps can be exemplified: a slurry of an electrolyte solution containing precipitated metal fibers is poured into a mold and allowed to settle, a supernatant liquid is removed, and the mixture is dried and, if necessary, pressurized and reduced.

[0109] The metal element used in the present production method is not particularly limited in type as long as the metal fiber can be produced by the present production method, and examples thereof include the metal elements described above.

[0110] When the metal fiber is produced by the above steps, it is preferred to perform electrolytic reduction in a state where the oily substance is attached to the surface of the cathode. By reducing the ions of the metal element in such a state, there is an advantage that the electrolytic reduction reaction performed on the electrode can be controlled.

[0111] As the oily substance attached to the surface of the cathode when manufacturing the metal fiber, various organic compounds having a viscosity that can be retained on the surface of the cathode after being attached to the surface of the cathode in addition to being poorly soluble or insoluble in water can be listed. As such organic compounds, under the condition of being poorly soluble or insoluble in water, aliphatic hydrocarbons, aromatic hydrocarbons, aliphatic alcohols, aromatic alcohols, aliphatic aldehydes, aromatic aldehydes, aliphatic ethers, aromatic ethers, aliphatic ketones, aromatic ketones, aliphatic carboxylic acids and their salts, aromatic carboxylic acids and their salts, amides of aliphatic carboxylic acids, amides of aromatic carboxylic acids, esters of aliphatic carboxylic acids, esters of aromatic carboxylic acids, etc. can be listed. Among them, higher fatty acids or their salts, esters or amides, or organic solvents mixed therewith are particularly preferred. Higher fatty acids can be monobasic acids or polybasic acids.

[0112] Examples of the higher fatty acid include saturated or unsaturated aliphatic carboxylic acids having preferably 10 to 25 carbon atoms, more preferably 10 to 22 carbon atoms, and further preferably 11 to 20 carbon atoms.

[0113] As methods for making the oily substance adhere to the surface of the above-mentioned cathode, there are listed, for example, a method of directly applying the oily substance to the surface of the cathode; a method of making the cathode adhere by immersing the cathode in a container containing the oily substance; a method of making the oily substance float on the liquid surface of the electrolyte and immersing the cathode from above to make the oily substance adhere to the surface of the cathode, etc. Furthermore, there is also the following method: suspending the oily substance in the electrolyte containing the cathode, stirring the suspended electrolyte, so that the suspended oily substance collides with the surface of the cathode and directly adheres to the surface of the cathode. In addition, in the case where the oily substance has the property of being soluble in a small amount in the electrolyte, even if the suspended oily substance does not directly contact the electrode, the oily substance temporarily dissolved in the electrolyte will be continuously adsorbed on the electrode surface, so that the result is the same degree of effect as when it is attached to the surface of the cathode.

[0114] When manufacturing the metal fiber, the amount of the oily substance attached to the surface of the cathode is preferably set to 1 g / m per unit surface area of ​​the cathode. 2 Above and 500g / m 2 Below, more preferably set to 3g / m 2 Above and 200g / m 2 Below, it is further preferably set to 5g / m 2 Above and 100g / m 2 the following.

[0115] Next, the obtained slurry containing metal fibers is allowed to stand to allow the metal fibers to settle, thereby manufacturing a metal nonwoven fabric. Specifically, the slurry containing the precipitated metal fibers is flowed into a water-impermeable mold, and the mold is allowed to stand to allow the metal fibers to settle. The size of the mold can be roughly the same as the size of the target metal nonwoven fabric, or a size larger than the size. By adjusting the amount of slurry flowing into the mold and the concentration of the metal fibers contained in the slurry, a metal nonwoven fabric having a desired liquid permeability, the size of the voids in the metal nonwoven fabric, and the porosity can be obtained.

[0116] Alternatively, as another method, the slurry containing the metal fibers can be filtered by a filter and directly dried, and after drying, the filter can be removed to produce the metal nonwoven fabric. Alternatively, as another method, the slurry containing the metal fibers can be sprayed on a substrate composed of metal or the like to form a film, or the metal nonwoven fabric can be produced by a spin coater.

[0117] In the above-mentioned film forming method, the structure of the metal nonwoven fabric can be controlled by applying an electric field or a magnetic field while forming the film.

[0118] It should be noted that as the above-mentioned metal fiber, a metal fiber whose surface is covered with a substance other than metal may be used. Alternatively, as the above-mentioned metal fiber, a metal fiber composed of a core portion composed of metal and a shell portion may be used, the core portion being composed of metal and the shell portion being arranged on the surface of the core portion and being composed of a metal other than the metal.

[0119] In addition, the metal nonwoven fabric may be covered with a substance other than metal after the metal nonwoven fabric is manufactured. Alternatively, the metal nonwoven fabric may be covered with a metal of a different type from the metal constituting the metal nonwoven fabric after the metal nonwoven fabric is manufactured.

[0120] After the metal fibers are deposited in the mold, the supernatant of the slurry is removed from the mold. The supernatant of the slurry can be removed by, for example, using a centrifuge, decanting the supernatant, or volatilizing the supernatant.

[0121] After the supernatant of the slurry is removed from the mold, the deposit remaining in the mold is dried under atmospheric pressure or in an inert gas atmosphere. In this process, the deposit is not completely dried, and the deposit coexists with a small amount of supernatant. In addition, the metal fibers in the deposit are very thin and long, so voids are generated in the deposit.

[0122] Then, as needed, a pressurizing machine can be used to pressurize the deposit in the thickness direction. Through this process, the thickness of the target metal nonwoven fabric can be adjusted. Then, by adjusting the pressure, time, temperature, etc. when the deposit is pressurized in the thickness direction, a metal nonwoven fabric with a desired liquid permeability, the size of the gap in the metal nonwoven fabric, and a porosity can be obtained. In the case where the deposit is pressurized in the thickness direction, for example, the deposit can be taken out from the mold, surrounded by a metal plate (spacer) with a target thickness, and pressurized from the metal plate. By adjusting the amount of the slurry flowing into the mold and the concentration of the metal fiber contained in the slurry, a metal nonwoven fabric with a desired liquid permeability, the size of the gap in the metal nonwoven fabric, and a porosity can be obtained.

[0123] From the perspective of obtaining a metal nonwoven fabric having the desired liquid permeability, the size of the voids within the metal nonwoven fabric, and the porosity, the pressure when the sediment is pressurized is preferably greater than 0.01 MPa and less than 50 MPa, more preferably greater than 1 MPa and less than 30 MPa, and further preferably greater than 1 MPa and less than 20 MPa.

[0124] From the same viewpoint as described above, the time for pressurizing the deposit is preferably 3 minutes to 5 hours, more preferably 10 minutes to 3 hours, and even more preferably 30 minutes to 2 hours.

[0125] When the deposit is pressurized, the deposit may be heated. Alternatively, the deposit may be pressurized without heating. When the deposit is heated, the temperature is preferably 500° C. or less, more preferably 350° C. or less, from the viewpoint of preventing excessive fusion between metal fibers.

[0126] After the deposit is dried, or after the deposit is pressurized in the thickness direction, the deposit is baked without pressurization under argon or nitrogen or hydrogen-containing atmosphere as needed, thereby fusing the intersections of the metal fibers in the deposit to obtain a metal non-woven fabric. When it is necessary to reduce the surface of the metal fiber during welding, the deposit is baked without pressurization under a hydrogen-containing atmosphere. Since the metal fiber is very long and thin, the surface of the metal fiber in the deposit is easily oxidized. Therefore, it is advantageous to bake the deposit to reduce the surface of the metal fiber. In addition, in the case of obtaining the metal fiber by the above-mentioned electrolysis method, by reducing and baking the deposit, there is also the advantage that at least a portion of the metal fiber in the deposit is easily welded.

[0127] From the viewpoint of sufficiently effectively reducing the surface oxide and fusing the metal fibers together, the time for baking the deposit is preferably 3 minutes to 24 hours, more preferably 30 minutes to 5 hours.

[0128] From the viewpoint of effectively reducing the metal and achieving appropriate fusion bonding between the metal fibers, the temperature for baking the deposit is preferably 800° C. or lower, and more preferably 150° C. or higher and 500° C. or lower.

[0129] The metal nonwoven fabric obtained in this way can also be cut into desired shapes. In addition, the metal nonwoven fabric obtained can be laminated in multiple layers to make a metal nonwoven fabric with a laminated structure.

[0130] In addition to the above-mentioned heat treatment, after the metal non-woven fabric is formed, it can also be plated as an electrode as a whole to cover the surface of the metal non-woven fabric with different types of metals, or the mechanical strength of the metal non-woven fabric can be improved by plating the same type of metal, or the size and porosity of the voids in the metal non-woven fabric can be controlled.

[0131] By manufacturing a metal nonwoven fabric using the above method, the metal nonwoven fabric as a whole has liquid permeability, the reactant in the liquid reaches the surface of the metal fiber constituting the metal nonwoven fabric in a short time, and a metal nonwoven fabric having a reaction area in which a reaction occurs immediately can be manufactured.

[0132] In the metal fiber in the metal nonwoven fabric, a polycrystalline structure is formed in which a plurality of crystals are connected along the length direction. In addition, the

[110] orientation of the crystal is not easy to be preferentially oriented in the length direction. Furthermore, the

[111] orientation of the crystal is easy to be preferentially oriented in the length direction, or the orientation direction of the crystal is easy to become random. It should be noted that, as described above, in the case where the surface of the core portion composed of metal in the metal fiber is stacked with a metal other than the metal, the metal other than the metal may be oriented in this way, or may not be oriented in this way.

[0133] The metal nonwoven fabric of the present invention obtained by the above method can be made into an electrochemical material that utilizes the liquid permeability of the metal nonwoven fabric and the physical properties and chemical properties of the metal fiber. For example, the metal nonwoven fabric of the present invention can be cut into a desired size and used as an electrode. Alternatively, the metal nonwoven fabric of the present invention can be combined with a fibrous body or a granular body of the same or different raw material as the nonwoven fabric and used as an electrode. In the electrode formed using the metal nonwoven fabric, for example, there are more gaps compared to the electrode formed based on the metal plate, so the reactivity with the liquid is improved. Thus, when the metal nonwoven fabric of the present invention is used as an electrode, compared with the porous materials used as the materials of the electrode that reacts with the liquid, the liquid permeability is improved, and the reacted substance can reach the surface of the metal fiber constituting the metal nonwoven fabric in a shorter time, so better reactivity can be obtained.

[0134] Therefore, the metal nonwoven fabric of the present invention can be used, for example, for biosensor electrodes, water electrolysis electrodes, carbon dioxide decomposition electrodes, organic synthesis electrodes, harmful substance decomposition electrodes, valuable substance synthesis electrodes, valuable substance collection electrodes, various battery current collectors, etc. Among them, the electrode formed by the metal nonwoven fabric can react quickly with a small amount of liquid, so it is a preferred example as a biosensor electrode.

[0135] In addition, when the metal nonwoven fabric of the present invention obtained by the above method is used as a selective adsorption material for chemical substances, the metal nonwoven fabric also plays an advantageous role in a reaction system in which no external current is applied, the reactant in the liquid contacts the metal fiber in the metal nonwoven fabric, and the components on the surface of the metal fiber are treated and reacted. Specifically, it is generally known that when an aqueous solution dissolved with hydrogen sulfide is contacted with the surface of a metal of copper, silver, gold, nickel, lead, palladium, platinum, cobalt, tin, iron, zinc or bismuth, the sulfide ions in the aqueous solution react with the surface of the metal to generate sulfide, so that harmful sulfide ions can be removed from the aqueous solution. When the metal nonwoven fabric of the present invention is used as a metal reacting with an aqueous solution, according to the metal nonwoven fabric, the liquid permeability is improved, and the reactant in the permeated liquid easily reaches the surface of the metal fiber constituting the metal nonwoven fabric, so the sulfide ions can be removed more effectively. According to the metal nonwoven fabric of the present invention, mercury present in, for example, an aqueous solution can also be effectively removed by the same method. It should be noted that even an article partially containing the metal nonwoven fabric of the present invention can also exert the same effect.

[0136] Therefore, the metal nonwoven fabric of the present invention can also be used, for example, as a filter for removing harmful substances from wastewater.

[0137] In addition, it is known that the antibacterial effect of metals such as copper can inhibit the proliferation of bacteria and viruses in liquids and gases. Therefore, by using a metal with an antibacterial effect as a part of the constituent material of the metal nonwoven fabric of the present invention, the contact frequency between bacteria and viruses as reactants and the surface of the metal fiber can be increased, thereby improving the efficiency of the antibacterial effect.

[0138] Therefore, the metal nonwoven fabric of the present invention can also be used, for example, as a filter for sterilizing bacteria and viruses in waste liquid discharged from medical institutions without heating, or as a filter for an air purifier for removing infectious viruses transmitted through the air.

[0139] Furthermore, due to the same mechanism, when the metal nonwoven fabric of the present invention is used as a heat transfer part of a heat exchanger using a liquid as a medium, for example, the efficiency of heat exchange can be improved.

[0140] Therefore, the metal nonwoven fabric of the present invention can also be used, for example, in efficient water-cooling type coolers for electronic devices.

[0141] As mentioned above, although this invention was demonstrated based on the preferred embodiment of this invention, this invention is not limited to the said embodiment.

[0142] The above-mentioned embodiments of the present invention include the following technical ideas.

[0143] [1] A metal nonwoven fabric comprising metal fibers and having liquid permeability, wherein the metal fibers have an average fiber diameter of 20 nm to 10 μm, and a distribution peak top diameter of voids measured by mercury porosimetry is 30 μm or less.

[0144] [2] The metal nonwoven fabric according to [1], wherein the distribution peak top diameter of the voids measured by mercury porosimetry is 0.01 μm or more.

[0145] [3] The metal nonwoven fabric according to [1] or [2], wherein, for a crystal of a metal constituting the metal fiber, when the length along the extending direction of the metal fiber is X and the length along the direction perpendicular to the extending direction is Y, the arithmetic mean of the ratio of X to Y at three boundary regions when the length is divided into four equal parts along the extending direction of the metal fiber, i.e., the value of X / Y, is 4 or less.

[0146] [4] The metal nonwoven fabric according to any one of [1] to [3], wherein the average length of the metal fibers is 0.5 μm or more and 5000 μm or less.

[0147] [5] The metal nonwoven fabric according to any one of [1] to [4], wherein the metal nonwoven fabric has an average thickness of 3 μm or more.

[0148] [6] The metal nonwoven fabric according to any one of [1] to [5], wherein the specific surface area is 0.02 m 2 / g or more and 22m 2 / g or less.

[0149] [7] The metal nonwoven fabric according to any one of [1] to [6], wherein the metal constituting the metal fibers is copper, silver, gold, nickel, lead, palladium, platinum, cobalt, tin, iron, zinc or bismuth, or an alloy containing these metals.

[0150] [8] The metal nonwoven fabric according to any one of [1] to [7], wherein the surface of the metal fiber is covered with a substance other than metal.

[0151] [9] The metal nonwoven fabric according to any one of [1] to [8], wherein the metal fiber is composed of a core portion and a shell portion, the core portion is composed of a metal, and the shell portion is arranged on the surface of the core portion and is composed of a metal other than the metal.

[0152]

[10] An electrode formed using the metal nonwoven fabric according to any one of [1] to [9].

[0153] Example

[0154] The present invention will be described in more detail below by way of examples. However, the scope of the present invention is not limited to these examples. Unless otherwise specified, "%" means "mass %".

[0155] [Example 1]

[0156] In this embodiment, a metal nonwoven fabric composed of copper is manufactured.

[0157] An electrolyte was prepared from copper sulfate and sulfuric acid in a manner such that the concentration of copper ions was 40 g / L and the concentration of free sulfuric acid was 19.6 g / L, and 800 mL of the electrolyte was added to an electrolytic cell of a size of 10 cm in width × 8 cm in depth × 12 cm in depth (capacity of about 1000 mL) and stirred. The liquid temperature of the electrolyte was set to 40°C.

[0158] As the cathode, a copper plate of 8 cm × 8 cm was used. Oleic acid was evenly coated on the surface of the cathode. The coating amount was set to 7 g / m 2 As the anode, a copper plate of 8 cm×8 cm was used. Both electrodes were suspended in the electrolytic cell so that the distance between the cathode and the anode was 8 cm.

[0159] Adjust the current density to 313A / m 2 , electrolysis was performed for 30 minutes. In this way, fibrous copper was electrolytically deposited on the surface of the cathode. The fibrous copper thus deposited was deposited on the electrode in a state of low aggregation, so it was peeled off and dispersed in 2-propanol to prepare a slurry.

[0160] 2.34 mL of the slurry (fibrous copper concentration 100 g / L) was poured into a mold (length 50 mm×width 12 mm×height 15 mm) with a Ti plate as a base, and the mold was allowed to stand at room temperature (25°C) for 1 hour to allow the precipitate to settle.

[0161] The supernatant liquid is removed and the remaining organic solvent is volatilized, thereby removing the solvent from the mold.

[0162] The deposit remaining in the mold was dried in a vacuum atmosphere at room temperature (25° C.) for 12 hours.

[0163] Then, the deposit was calcined without pressure in a hydrogen atmosphere (3 vol% H2 and the remainder N2) to obtain a metal nonwoven fabric. The calcination was performed at 350°C for 1.5 hours. The obtained metal nonwoven fabric was observed using a SEM, and the metal fibers constituting the metal nonwoven fabric were observed. Each end of the metal fiber was tapered and bent.

[0164] [Comparative Example 1]

[0165] A Cu (copper) metal porous body (MF-30) manufactured by Nagamine Seisakusho Co., Ltd. was used as the metal nonwoven fabric of Comparative Example 1. MF-30 was observed using a SEM, and it was found that MF-30 was a sponge-like porous body.

[0166] [Comparative Example 2]

[0167] A Cu (copper) metal porous body (MF-80A) manufactured by Nagamine Seisakusho Co., Ltd. was used as the metal nonwoven fabric of Comparative Example 2. MF-80A was observed using a SEM, and it was found that MF-80A was a sponge-like porous body.

[0168] [Example 2]

[0169] 0.78 mL of the same slurry as that produced in Example 1 was added to a mold with a Ti plate as the base plate in the same manner as the slurry used in the embodiment, and the mold with the deposit was dried under a vacuum atmosphere using the same method as the embodiment, and then the deposit was taken out of the mold. The deposit was surrounded by a copper plate with a thickness of 100 μm, and the deposit was pressurized at 20 MPa in the thickness direction from the plate. The pressurization of the deposit was carried out at room temperature (25°C) for 0.5 hours. In addition, a metal nonwoven fabric was obtained in the same manner as in Example 1.

[0170] [Example 3]

[0171] The electrolyte was prepared from copper sulfate and sulfuric acid so that the concentration of copper ions was 10 g / L and the concentration of free sulfuric acid was 5 g / L. The current density was set to 156 A / m 2 , and power is applied for 30 minutes. In this way, fibrous copper is electroprecipitated on the surface of the cathode. The fibrous copper is dispersed in 2-propanol to form a slurry. 4.54 mL of the slurry (concentration 27 g / L) is filtered through a 45 mm silica filter (inner diameter 35 mm). Take it out while it is attached to the filter and evaporate the residual solvent. Then, dry it under a vacuum atmosphere and roast it under a hydrogen-containing atmosphere in the same manner as in Example 1. Finally, peel off the silica filter from the formed copper non-woven fabric.

[0172] [Comparative Example 3]

[0173] A copper fiber sheet manufactured by Tomogawa Paper Co., Ltd. was used as the metal nonwoven fabric of Comparative Example 3. The copper fiber sheet was observed using a SEM, and the copper fiber sheet was found to be a porous body composed of copper fibers. Since the adhesive tape was attached, it was immersed in ethanol to separate from the adhesive tape.

[0174] [Example 4]

[0175] An electrolyte was prepared from copper sulfate and sulfuric acid in a manner such that the concentration of copper ions was 40 g / L and the concentration of free sulfuric acid was 19.6 g / L, and 800 mL of the electrolyte was added to an electrolytic cell of a size of 10 cm in width × 8 cm in depth × 12 cm in depth (capacity of about 1000 mL) and stirred. Instead of applying oleic acid on the surface of the cathode, 30 mL of oleic acid was further added to the electrolyte. The electrolyte was stirred so that oleic acid was suspended in the entire electrolyte. The liquid temperature of the electrolyte was set to 40°C.

[0176] A metal nonwoven fabric was obtained in the same manner as in Example 1 except for the above. The obtained metal nonwoven fabric was observed using a SEM, and metal fibers constituting the metal nonwoven fabric were observed. Each end of the metal fiber was tapered and curved.

[0177] [Evaluation 1]

[0178] The average fiber diameter and average length of the metal fibers constituting the samples obtained in Examples 1 to 4 and the sample prepared as Comparative Example 3 were measured by the above-mentioned method. It should be noted that the samples used in Comparative Examples 1 and 2 were sponge-like porous bodies (hereinafter also referred to as "sponge metals"), so the measurement was omitted.

[0179] In addition, the value of X / Y was calculated by the above method for the crystals of the metal constituting the metal fibers in the samples obtained in Examples 1 to 4. It should be noted that the value of X / Y was not calculated in Comparative Examples 1 to 3. The reason for this is that the samples used in Comparative Examples 1 and 2 were sponge-like metals, and the value of X / Y could not be proven to reflect the shape of the crystals. This is because the average fiber diameter of the sample used in Comparative Example 3 was a large value of 20 μm, so the value of X / Y did not reflect the shape of the crystals, similarly to Comparative Examples 1 and 2.

[0180] In addition, for the samples obtained in Examples 1 to 4 and Comparative Examples 1 to 3, the distribution peak diameter of the voids was measured by the above method using the mercury intrusion method (when the voids were 30 μm or less), or the average value of the equivalent spherical diameter of the pores obtained by dividing the voids by image analysis measured by X-ray CT was measured by the above method (when the voids exceeded 30 μm), thereby obtaining the size of the voids in the metal nonwoven fabric constituting the sample or the size of the voids in the sponge-like metal. In addition, the porosity was measured by the above method.

[0181] Furthermore, the average thickness, apparent density and specific surface area of ​​the samples obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were measured by the above-mentioned methods. 2 / g or more, the specific surface area of ​​the metal nonwoven fabric was measured by krypton gas adsorption-BET multipoint method using a specific surface area / pore size distribution measuring device BELSORP-max manufactured by BEL Japan Inc. as described above. 2 The specific surface area of ​​the metal nonwoven fabric of 100 g was measured by X-ray CT using a nanofocus X-ray CT scanner SKYSCAN AN2214 manufactured by Bruker. The apparent density of the sample was determined from the volume V1 and mass of the sample by the above method.

[0182] These results are shown in the following Table 1. In addition, since the length of the metal fiber in the sample of Comparative Example 3 was so long that it could not be measured by the above-mentioned method, it was described as "continuous" in Table 1.

[0183] [Evaluation 2]

[0184] Using the samples of Examples 1 to 4 and Comparative Examples 1 to 3, the liquid permeability of the samples was evaluated based on the above-mentioned method.

[0185] The average amount of water absorbed per unit volume based on the outer dimensions of the sample in a dry state was calculated and the value was 0.4 mL / cm 3 The above samples were evaluated as having liquid permeability, and the value was less than 0.4 mL / cm 3 The results are shown in Table 1.

[0186] The samples of Comparative Examples 1 to 3 obtained as commercial products were immersed in a 0.1 mol / L sodium hydroxide aqueous solution for 5 minutes and then immersed in a 4-fold diluted nitric acid aqueous solution for 3 minutes before measurement to clean the surface.

[0187] [Evaluation 3]

[0188] Evaluation was performed to confirm the reachability of the reactant to the metal fiber or surface constituting the samples of Examples 1 to 4 and Comparative Examples 1 to 3. The amount of electricity (electrochemically detected amount of electricity) (mC) required for oxidation of glucose in the aqueous solution during electrolysis was determined by the following method using the samples of Examples 1 to 4 and Comparative Examples 1 to 3. The results are shown in Table 1.

[0189] [Measurement of the amount of electricity required for the oxidation of glucose]

[0190] The samples of Examples 1 to 4 and Comparative Examples 1 to 3 were cut into a size of 5×20 mm and placed on a 48×30 mm plastic plate with a glass fiber filter (GA-100 manufactured by ADVANTEC) placed on top. The glass fiber filter was cut into the size of the plastic plate in advance. It should be noted that the samples of Comparative Examples 1 to 3 obtained as commercial products were immersed in a 1 mol / L sodium hydroxide aqueous solution for 5 minutes before measurement, and then immersed in a 4-fold diluted nitric acid aqueous solution for 3 minutes to clean the surface. The samples of Examples 1 to 2 and 4 were also washed before measurement, but the immersion in the 4-fold diluted nitric acid aqueous solution was set to 15 seconds. In addition, the sample of Example 3 was also washed before measurement, but was not immersed in a 4-fold diluted nitric acid aqueous solution. These samples were used as detection electrodes for detecting glucose. It should be noted that the average thickness of each sample (metal nonwoven fabric or sponge metal) cut out is as shown in Table 1.

[0191] A Pt wire having a diameter of about 0.5 mm was arranged along the longitudinal direction of the detection electrode at a distance of about 4.5 mm from the side edge of the detection electrode to serve as a counter electrode.

[0192] A 48 mm x 25 mm, 1.5 mm thick silicone rubber with an elliptical hole of 15 mm in width and 10 mm in length and a 0.8 mm thick plastic plate with the same hole and the same size as the silicone rubber were placed on the top. The side edge of the sample (the side with the counter electrode) was arranged to overlap the straight line representing the short diameter of the elliptical hole, and fixed with a clamp.

[0193] As the standard electrode, a silver / silver chloride electrode with an outer diameter of 3 mmφ and a ceramic plug embedded in the front end was used, and it was arranged on the detection electrode side between the detection electrode and the counter electrode. The front end of the standard electrode was lightly contacted with the surface of the glass fiber filter. The electrical connection to the detection electrode was made by connecting with an alligator clip from the part extending from the plastic plate that became the cover plate.

[0194] Before the detection, 1000 μL of a 0.1 mol / L sodium hydroxide aqueous solution was added to the detection electrode, the standard electrode, and the silver / silver chloride electrode to wet the three electrodes and achieve electrical conduction between the electrodes.

[0195] Next, the detection electrode is subjected to a voltage of -0.2 to 0.8 V (relative to the silver / silver chloride standard electrode) applied at 50 mV / s for 5 times and scanned to form an oxide film on the copper surface of the detection electrode. Even if the operation is repeated 5 times, if the difference between the current value of the last repetition at a potential of 0.8 V and the current value of the previous repetition is greater than 0.05 mA, the operation is further repeated. The operation is repeated until the difference between the current value of the last repetition at a potential of 0.8 V and the current value of the previous repetition is less than 0.05 mA. After that, a paper twist made using a JK wiper (manufactured by NIPPON PAPERCRECIA CO., LTD.) is applied to the upper surface of the detection electrode to absorb the solution seeping from the detection electrode. The glass fiber filter serving as the base is kept moist.

[0196] Next, electricity is applied in such a way that the potential of the detection electrode becomes 0.55V (relative to the silver / silver chloride standard electrode). 20μL of a 0.1mol / L sodium hydroxide aqueous solution is added thereto as an auxiliary electrolyte. Then, a 0.1mol / L sodium hydroxide aqueous solution in which a specified amount of glucose (5440μmol / L) is dissolved is added dropwise to the detection electrode using a micropipette. As in Examples 1 and 4 and Comparative Examples 1 and 2, when the thickness of the detection electrode is about 1mm, 20μL of the aforementioned sodium hydroxide aqueous solution is added to the detection electrode. As in Examples 2 and 3 and Comparative Example 3, when the thickness of the detection electrode is about 0.1mm, 2μL of the aforementioned sodium hydroxide aqueous solution is added to the detection electrode.

[0197] As glucose permeates into the detection electrode, glucose undergoes a catalytic reaction with copper oxide present on the surface of the detection electrode, glucose is oxidized, and an oxidation current flows between the detection electrode and the counter electrode. Therefore, the amount of electricity required for oxidation of glucose can be detected.

[0198] The time-dependent change of the oxidation current flowing from the moment the sodium hydroxide aqueous solution in which glucose was dissolved was added was monitored. The amount of electricity detected during the 30-second period from the addition of the sodium hydroxide aqueous solution in which glucose was dissolved was determined. In the case where 20 μL of the sodium hydroxide aqueous solution was added to the detection electrode having a thickness of about 1 mm in Examples 1 and 4 and Comparative Examples 1 and 2, the peak of the oxidation current was tailed even after 30 seconds from the addition, but the accumulation of electricity was always completed at 30 seconds.

[0199] [Table 1]

[0200]

[0201] As shown in Table 1, when comparing Examples 1 and 4 with Comparative Examples 1 and 2, which have substantially the same average thickness, the metal nonwoven fabrics obtained in Examples 1 and 4 have higher liquid permeability than the samples obtained in Comparative Examples 1 and 2, and the value of the electrochemically detected electric quantity of glucose is greatly improved. In addition, when comparing Examples 2 and 3 with Comparative Example 3, which have the same average thickness, the metal nonwoven fabrics obtained in Examples 2 and 3 have higher liquid permeability than the sample obtained in Comparative Example 3, and the value of the electrochemically detected electric quantity of glucose is greatly improved. It can be seen that the liquid permeability of the metal nonwoven fabrics obtained in Examples 1 to 4 is higher than that of the samples of Comparative Examples 1 to 3. It can be further seen that the metal nonwoven fabrics obtained in Examples 1 to 4 are composed of slender metal fibers, unlike the samples of Comparative Examples 1 to 3, so the reacted substance in the liquid reaches the surface of the metal fibers constituting the metal nonwoven fabric in a short time, and the desired reaction is effectively carried out. Therefore, it can be seen that the metal nonwoven fabrics obtained in Examples 1 to 4 have better performance as electrodes than the samples of Comparative Examples 1 to 3.

[0202] Industrial Applicability

[0203] According to the present invention, it is possible to provide a metal nonwoven fabric having improved liquid permeability and having a function in which a reactant in the permeated liquid easily reaches the surface of metal fibers constituting the metal nonwoven fabric.

Claims

1. A metal nonwoven fabric comprising metal fibers and having liquid permeability, The average fiber diameter of the metal fibers is greater than or equal to 20 nm and less than or equal to 10 μm. The distribution peak top diameter of voids measured by mercury porosimetry is 30 μm or less.

2. The metal nonwoven fabric according to claim 1, wherein: The distribution peak top diameter of voids measured by mercury porosimetry is 0.01 μm or more.

3. The metal nonwoven fabric according to claim 1, wherein: For the crystal of the metal constituting the metal fiber, when the length along the extending direction of the metal fiber is set to X and the length along the direction orthogonal to the direction is set to Y, the arithmetic mean of the ratio of X to Y in three boundary areas when the length is divided into four equal parts along the extending direction of the metal fiber, that is, the value of X / Y is less than 4.

4. The metal nonwoven fabric according to claim 1, wherein: The average length of the metal fibers is greater than or equal to 0.5 μm and less than or equal to 5000 μm.

5. The metal nonwoven fabric according to claim 1, wherein: The average thickness of the metal nonwoven fabric is 3 μm or more.

6. The metal nonwoven fabric according to claim 1, having a specific surface area of ​​0.02 m 2 / g or more and 22m 2 / g or less.

7. The metal nonwoven fabric according to claim 1, wherein: The metal constituting the metal fiber is copper, silver, gold, nickel, lead, palladium, platinum, cobalt, tin, iron, zinc or bismuth, or an alloy containing these metals.

8. The metal nonwoven fabric according to claim 1, wherein: The surface of the metal fiber is covered with a substance other than metal.

9. The metal nonwoven fabric according to claim 1, wherein: The metal fiber is composed of a core portion and a shell portion, the core portion is composed of metal, and the shell portion is arranged on the surface of the core portion and is composed of a metal other than the metal. 10 . An electrode formed using the metal nonwoven fabric according to claim 1 .

Citation Information

Patent Citations

  • Non-woven collector, method of fabricating a battery with the same and system for fabricating the same

    KR1020140131115A

  • Fine metal linear body

    TW202208085A

  • Reinforced porous metal foil and process for production thereof

    US20130216849A1

  • High surface area, highly conductive three-dimensional porous electrodes for electrochemical reaction applications

    US20190305322A1

  • Metal non-woven fabric electrode having dopamine-based monomer polymerized on surface thereof, and surface modification method therefor

    US20200052306A1